32Do the risks of Lynch syndrome-related cancers depend on the parent-of-origin of the mutation?. (2nd September 2021) - Gemechu, Shimelis; van Vliet, Christine M.; Win, Aung Ko; Figueiredo, Jane C.; Marchand, Loic Le; Gallinger, Steven; Newcomb, Polly A.; Hopper, John L.; Lindor, Noralane M.; Jenkins, Mark A.; Dowty, James G.
Abstract: Background: Individuals who carry pathogenic mutations in DNA mismatch repair (MMR) genes have high risks of cancer, and small studies have suggested that these risks depend on the sex of the parent from whom the mutation was inherited. We have conducted the first large study of such a parent-of-origin effect (POE). Methods: Our study was based on all MMR gene mutation carriers and their relatives in the Colon Cancer Family Registry, comprising 18, 226 people. The POE was estimated as a hazard ratio (HR) using a segregation analysis approach that adjusted for ascertainment. HR = 1 corresponds to no POE and HR > 1 corresponds to higher risks for maternal mutations. Results: For all MMR genes combined, the estimated POE HRs were 1.02 (95% confidence interval (CI) 0.75-1.39, p = 0.9) for male colorectal cancer, 1.12 (95% CI 0.81-1.54, p = 0.5) for female colorectal cancer and 0.84 (95% CI 0.52-1.36, p = 0.5) for endometrial cancer. Separate results for each MMR gene were similar. Conclusions: Despite being well-powered, our study did not find any evidence that cancer risks for MMR gene mutation carriers depend on the parent-of-origin of the mutation. Based on current evidence, we don't recommend that POEs be incorporated into the clinical guidelines or advice for such carriers. Key messages: MMR gene mutations inherited from the maternal and paternal side confer similar risks of developing colorectal and endometrial cancer.